Optimization of microalgae growth for biofuel production using a new empirical dynamic model. Issue 10 (26th November 2021) - Humphrey, Ibifubara; Chendo, Michael A. C.; Njah, Abdulahi N.; Nwankwo, Dike I.
Abstract: This study involves modeling the growth of Tetradesmus sp. in a laboratory batch culture chamber under red, blue and magenta lights at intensities of 1000 to 5000 lux as well as under artificial white light and sunlight (at natural intensities). The growth, which is determined by measuring the optical density at 680 nm, is found to be highest at 5000 lux with values of 0.997 (Magenta), 0.793 (blue) and 0.777 (red) which are compared to 0.799 (sunlight) and 0.815 (artificial white light). Furthermore, an empirical dynamic model is developed for the estimation of the microalgae growth and implemented with Matlab Simulink. The model is validated by calculating mean absolute percentage error (MAPE), correlation coefficient (R), root mean square error (RMSE), mean square error (MSE), and mean absolute error (MAE) and comparing the values with those of some existing (Logistic and Monod) models. The values of R are found to be 0.9834 (new model), 0.7119 (Logistic model) and 0.8177 (Monod model), showing that the new model has the highest correlation with the experimental data. Thus, the growth of microalgae ( Tetradesmus sp.) is greatly enhanced by high intensity magenta light and is best described by the new empirical model.